Identification of wetland areas in the context of agricultural development using remote sensing and GIS [Identificación de áreas de humedal en el contexto del desarrollo agrícola usando teledetección y SIG] (2017)
This study aims to determine the wetland potential on a pixel basis on the floodplain of the Leon River: hydrology, hydrophytic vegetation and hydromorphic soils were taken into account. Field measurements and spatially explicit models were used to model surface hydrology and piezometric levels. Satellite data were used to derive inundated areas and vegetation. Existing maps from the national geographic institute (IGAC) were used to define the spatial distribution of hydromorphic soils. Special attention was paid to agricultural infrastructure, levees and diversion channels used to modify surface hydrology in order to promote plantations and cattle grazing. A total of 536 km2 meet one or more wetland conditions according to biophysical variables, but only 393 km2 were selected, using logical rules, as wetland pixels. The combination of biophysical variables to define wetland potential is discussed in terms of the spatial distribution and the implications for environmental resource management. © The author; licensee Universidad Nacional de Colombia.